Predictors of ultimate postoperative cervical sagittal alignment in main thoracic adolescent idiopathic scoliosis: A long-term follow-up study. Issue 49 (December 2017) - Zhang, Zhen; Liu, Zhen; Zhu, Zezhang; Qiu, Yong
Abstract : Abstract: This is a retrospective study. The aim of this study was to access sagittal compensatory mechanism of the cervical spine in thoracic adolescent idiopathic scoliosis (T-AIS) before and after posterior spinal fusion and to identify preoperative or immediate postoperative radiographic parameters that can predict the ultimate cervical sagittal alignment (CSA) after long-term follow-up. A retrospective study was performed on 44 T-AIS patients treated with posterior spinal fusion and with at least 5 years of follow-up. Preoperative, immediate postoperative and latest follow-up radiographs were reviewed measuring cervical lordosis (CL), cervical sagittal vertical axis (CSVA), upper thoracic kyphosis (UTK), main thoracic kyphosis (MTK), global thoracic kyphosis (GTK), lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt (PT), and sacral slope (SS). Pearson correlation analysis, stepwise multilinear regression analysis, and receiver operator characteristic (ROC) curve were performed to define the relationship between ultimate CL and preoperative or immediate postoperative radiographic parameters. CL significantly improved from 6.6 ± 8.8 degree kyphosis preoperatively to 3.8 ± 8.7 degree kyphosis immediate postoperatively and to 0.5 ± 7.3 degree lordosis at the latest follow-up. Pre- and postoperative CSVA showed no significant difference. Pearson correlation coefficient test showed that CL was only correlated to T1 slope and UTK before surgery, whereas it was correlated to T1 slope, UTK, and GTK after surgery. The following equation was developed to estimate the ultimate CL: ultimate CL = −2.792 + 0.510 × Preop CL + 0.531 × Postop T1 slope. Furthermore, ROC curve showed that preoperative CL ≥−4.5 degree was strongly predictive and postoperative T1 slope ≥11.3 degree was moderately predictive of lordotic cervical spine after long-term follow-up. For T-AIS patients, CL significantly increased after surgery with the restoration of the global and regional sagittal profile. The sagittal compensatory mechanism of the cervical spine before surgery is different from that after surgery. In these patients, preoperative CL and immediate postoperative T1 slope could be predictors of the ultimate CSA after long-term follow-up.